Efficacy of RUTI® immunotherapy against active tuberculosis in a mouse model challenges the Koch phenomenon - Soldevilla, Pablo; Buisan, Anna; Diaz, Jorge; Saladrigas, Sergi; Rosales, Yaiza; Arias, Lilibeth; Jimenez-Melsio, Alexandra; Vilaplana, Cristina; Amat Fabregat, Merce; Cardona, Pere-Joan (Frontiers in Tuberculosis, 2023)
Objectives: The objective of this study was to evaluate the safety and efficacy of the therapeutic vaccine RUTI® with or without the standard of care (SOC) chemotherapy for TB in an experimental murine model. Methods: We have assessed the efficacy of RUTI®, a vaccine based on pasteurized and freeze-dried cell-wall fragments from Mycobacterium tuberculosis (Mtb), the SOC for sensitive TB (Isoniazid, Rifampicin, Ethambutol and Pyrazinamide) in the murine active TB model in C3HeB/FeJ strain (Kramnik model). We have evaluated the bacillary load in lungs and spleen, immune response against specific Mtb antigens (PPD, HSP16.3, ESAT-6 and PsTS1), and lung damage in paraffined tissues for qualitative and quantitative analysis. Results: RUTI® significantly reduces the pulmonary damage (x3), the bacterial burden in lungs (1.5 log10) and spleen (1 log10); and maintains the cellular immune response against ESAT-6, compared to SOC. There was also an additive effect when administered in combination with SOC, increasing the reduction of the lung damage (x2), the bacillary load in lungs (1 log10) and increasing the immune response against PPD, HSP16.3 and PsTS1. Discussion: Therapeutic vaccination against TB has been avoided for decades due to fear for toxicity through the Koch phenomenon. This data shows for the first time the safety of immunotherapy with Mtb antigens in an active TB model, adding efficacy to SOC. It encourages the beginning of clinical studies to evaluate the safety and efficacy of RUTI® in TB patients to improve their health, reduce its potential infectiousness and reduce the length of treatment.